2014
DOI: 10.1016/j.jcss.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Tight bounds for parameterized complexity of Cluster Editing with a small number of clusters

Abstract: In the Cluster Editing problem, also known as Correlation Clustering, we are given an undirected n-vertex graph G and a positive integer k. The task is to decide if G can be transformed into a cluster graph, i.e., a disjoint union of cliques, by changing at most k adjacencies, i.e. by adding/deleting at most k edges. We give a subexponential-time parameterized algorithm that in time 2 O( √ pk) + n O(1) decides whether G can be transformed into a cluster graph with exactly p cliques by changing at most k adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Respectively, Low GF(2)-Rank Approximation asks whether it is possible to edit at most k entries of the input matrix to obtain a matrix of rank at most r. In P-Matrix Approximation, we ask whether we can edit at most k elements to obtain a P-matrix. A lot of work in graph algorithms has been done on graph editing problems, in particular parameterized subexponential time algorithms were developed for a number of problems, including various cluster editing problems [21,24].…”
Section: Related Workmentioning
confidence: 99%
“…Respectively, Low GF(2)-Rank Approximation asks whether it is possible to edit at most k entries of the input matrix to obtain a matrix of rank at most r. In P-Matrix Approximation, we ask whether we can edit at most k elements to obtain a P-matrix. A lot of work in graph algorithms has been done on graph editing problems, in particular parameterized subexponential time algorithms were developed for a number of problems, including various cluster editing problems [21,24].…”
Section: Related Workmentioning
confidence: 99%
“…However, such type of algorithms are rarely observed in other contexts except for very few examples [51,52] .…”
Section: Subexponential Algorithms and Polynomialtime Approximation Smentioning
confidence: 99%
“…Ghosh et al [22] showed that Split Completion is solvable in the same running time. Although Komusiewicz and Uhlmann [27] showed that we cannot expect Cluster Editing to be solvable in subexponential parameterized time, as shown by Fomin et al [17], when the number of clusters in the target graph is sublinear in the number of allowed edits, this is possible nonetheless.…”
Section: Introductionmentioning
confidence: 97%